Diminazene Aceturate Liposomes: Morphometric and Biochemical Liver, Kidney, and Spleen of Rats Infected with Trypanosoma evansi - Oliveira C.B. (2014)
© 2014 Elsevier GmbH.The aim of this study was to evaluate the effect of treatment with liposomal (L-DMZ) and conventional (C-DMZ) diminazene aceturate formulations on hepatic and renal functions of rats, experimentally infected with Trypanosoma evansi. For this purpose, 72 Wistar rats (Rattus norvegicus) were divided into six groups (A, B, C, D, E, and F). Each group was subdivided into two other subgroups in order to assess the biochemical and histological results on days 7 and 40 post-treatment (PT). Treatments were carried out based on two different therapeutic protocols: L-DMZ and C-DMZ at 3.5mg/kg-1, single dose (groups C and D), and five successive doses within intervals of 24h (groups E and F). Groups A and B corresponded to uninfected and infected (without treatment) animals, respectively. Sample collections were held on days 7 and 40 PT for the assessment of hepatic [alkaline phosphatase (AP), alanine transferase (ALT), albumin, gamma glutamil transferase (GGT) and renal functions (creatinine and urea). Additionally, the histology of fragments of liver, kidney, and spleen was performed. Animals in group B showed a significant increase in AP, GGT, ALT, and urea when compared with group A. On day 7 post-inoculation (PI), the biochemical analysis showed a reduction (P<0.05) of AP and GGT, while the levels of urea were increased in groups C, D, E, F. On day 40 PT, ALT was increased in these same groups when compared with group A. In histopathology, changes in liver samples were observed on day 7 PT in groups D and F, especially regarding the area and density of the hepatocytes. Renal analysis exhibited changes in glomerular space, glomerular, and corpuscular areas in group E. Therefore, these results allowed us to conclude that the treatment with L-DMZ and C-DMZ led to variable biochemical changes, which defined the functions of the liver and kidneys of treated animals, since the main histopathology alterations were observed in animals treated with liposomes, at their higher dosages. Thus, treatments with L-DMZ and C-DMZ in five consecutive doses were effective although being followed by liver toxicity.